Inkjet Printing of Liquid Silicon. Issue 23 (21st October 2020) - Masuda, Takashi; Nakayama, Maui; Saito, Kimihiko; Katayama, Hirotaka; Terakawa, Akira
Abstract: A precursor solution for semiconducting Si called liquid Si (liq‐Si) is synthesized, and semiconducting Si is inkjet‐printed. Satisfactory inkjet discharge is achieved using liq‐Si consisting of liquid‐phase polysilane with an average molecular weight of 2500 g mol −1 . The printed liq‐Si is converted into amorphous Si by heating at 400 °C. The resulting Si film has a flat surface with a root‐mean‐square roughness of 0.8 nm. These results are extended to n‐ and p‐type Si films by synthesizing liq‐Si chemically doped with P and B compounds, respectively. Liq‐Si inkjet printing produces Si patterns without using traditional photolithography processes, opening up the field of printed Si electronics. Abstract : A precursor solution for semiconducting Si called liquid‐Si is synthesized and printed by an inkjet method. Well‐defined printed patterns are converted into amorphous or polycrystalline Si by heat treatment. The Si printing technology is also extended to p‐ and n‐type Si film by synthesizing liquid‐Si chemically doped with B and P compounds, respectively.